2018
DOI: 10.1080/14614103.2018.1482598
|View full text |Cite
|
Sign up to set email alerts
|

Archaeological and Historical Materials as a Means to Explore Finnish Crop History

Abstract: In Northern Europe, barley (Hordeum vulgare L.) has been cultivated for almost 6000 years. Thus far, 150-year-old grains from historical collections have been used to investigate the distribution of barley diversity and how the species has spread across the region. Genetic studies of archaeobotanical material from agrarian sites could potentially clarify earlier migration patterns and cast further light on the origin of barley landraces. In this study, we aimed to evaluate different archaeological and historic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…Indeed, Forsberg et al (2015) studying as few as six individuals from each of 31 historical accessions from all over Fennoscandia and Denmark, showed how six-row barley from northernmost Fennoscandia was, as a group, genetically differentiated from six-row barley elsewhere in the region. Similar results were obtained by Lempiäinen-Avci et al (2018) focusing on Finnish barley.…”
Section: Introductionsupporting
confidence: 86%
“…Indeed, Forsberg et al (2015) studying as few as six individuals from each of 31 historical accessions from all over Fennoscandia and Denmark, showed how six-row barley from northernmost Fennoscandia was, as a group, genetically differentiated from six-row barley elsewhere in the region. Similar results were obtained by Lempiäinen-Avci et al (2018) focusing on Finnish barley.…”
Section: Introductionsupporting
confidence: 86%
“…Since the initial report of aDNA in charred cereal grains (Allaby et al, 1994), there has been extensive debate regarding the extent to which DNA is preserved in this type of material. Early conclusions that aDNA is present in, at best, only a few grains from an archaeobotanical sample (Allaby et al, 1997;Brown, 1999) have been confirmed by several papers reporting negative results (Brown et al, 1998;Brown, 1999;Oliveira et al, 2012;Fernandez et al, 2013;Nistelberger et al, 2016;Lundstrom et al, 2018;Lempiäinen-Avci et al, 2020). Recently, the ability of DNA to withstand the heating conditions needed to produce charred archaeobotanical material has been questioned (Nistelberger et al, 2016;Lundstrom et al, 2018), but this view is arguably over-pessimistic, requiring that the numerous positive reports of aDNA in charred wheat, barley and rice remains (Allaby et al, 1994(Allaby et al, , 1997(Allaby et al, , 1999Blatter et al, 2002;Schlumbaum et al, 1998;Fernandez et al, 2013;Bilgic et al, 2016;Tanaka et al, 2010, Castillo et al, 2016Ciftci et al, 2019) be dismissed as illusory.…”
Section: Amplification Of Dna From Charred Ngw Accessionsmentioning
confidence: 90%
“…Utilization of a PCR test for taxonomic identification of the NGW would require analysis of ancient DNA (aDNA), which is challenging with charred cereal specimens due to the extensive DNA breakdown that occurs during the heating process involved in preservation of these remains (Threadgold and Brown, 2003). It is clear that with many charred grains the degree of transformation to carbon is such that preserved aDNA cannot be detected by PCR (Brown et al, 1998;Brown, 1999;Oliveira et al, 2012;Fernandez et al, 2013;Lundstrom et al, 2018;Lempiäinen-Avci et al, 2020) or by next generation sequencing (Nistelberger et al, 2016). This does not, however, negate the conclusions of early work that some grains in some charred samples retain DNA fragments that are sufficiently intact to be amplified by highly specific and sensitive PCR tests (Brown, 1999), as shown by the numerous reports of aDNA sequences obtained from charred cereal samples (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The remaining SNPs were chosen from the 384 C‐SNP set developed for European landraces (Moragues et al., 2010) from the BOPA1 array (Kota et al., 2008). The SNPs chosen were distributed across all seven barley chromosomes and had previously be verified to be polymorphic in Nordic barley (Denmark, Sweden, Norway and Finland) (Forsberg et al., 2015; Lempiäinen‐Avci et al., 2020). Following genotyping, two markers, 11_11059 and 11_20897, were removed due to poor success rate (24.5 and 14.2% success rate, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…The majority of the markers had previously been genotyped in historical two‐row landrace barley from the Nordic area (Norway, Sweden, and Finland; Lempiäinen‐Avci et al., 2020; Hagenblad & Leino, unpublished data, 2011; Supplemental Table S3). Data from these accessions were used to compare the Chevalier barley genotyped in this study with landrace barley of the two‐row type.…”
Section: Methodsmentioning
confidence: 99%